P14.52 Differential methylation of a single CpG site in the CD95 ligand promoter affects gene activity and correlates with invasiveness of glioma cells. (6th September 2019) - Merz, C; Sykora, J; Krendyukov, A; Wiestler, B; Gieffers, C; Wick, W
Abstract: BACKGROUND: CD95 ligand (TNFSF6/APO-1L/FASLG) is a member of the Tumour Necrosis Factor Super Family (TNF-SF). Binding of the CD95 ligand (CD95L) to CD95 expressed on intrinsically apoptosis-resistant cancer cells like glioblastoma, triggers intracellular signal transduction resulting in increased tumour growth and invasiveness. A phase II clinical trial in patients with recurrent glioblastoma (NCT01071837) treated by Asunercept (a recombinant glycosylated fusion protein, which selectively binds and inhibits CD95L activity) was followed by a genome-wide assessment of DNA methylation. Here, a CpG-site (designated CpG2) within the CD95L-promotor was identified, exhibiting differential methylation between Asunercept responders (PFS>5 months) and non-responders (PFS < 2 months) with a significant survival benefit achieved in Asunercept treated patients with low CpG2 methylation (HR 0.34, p = 0.025). METHODS AND RESULTS: We have performed in vitro studies to establish a link between the CpG2 methylation status and cellular characteristics of glioblastoma cell lines. A 3-dimensional spheroid invasion assay showed that highly methylated glioma cells like T98G did not grow and invade the surrounding matrix as aggressively compared to spheroids formed from low methylated glioma cells, e.g. U87-MG. Invasive growth of U87-MG spheroids in these assays was suppressed in the presence of Asunercept. A 1 kb fragment of the T98G CD95L promoter was subsequently cloned into a CpG-free reporter gene plasmid. Luciferase-based reporter gene assays of in vitro methylated and unmethylated plasmids in transfected HEK cells indicate that the CD95L promoter, despite the observed sparseness of CpG sites, is at least partially regulated by its methylation level. Furthermore, mutational disruption of the CpG2 site completely silenced reporter gene activity in vitro, which insinuates that both methylation level and gene promoter sequence are involved in regulation of the CD95L gene. CONCLUSION: In essence, the level of CpG2 methylation correlates to aggressiveness of glioma derived cancer spheroids in vitro, and methylation of the CD95L promoter in glioblastoma tissue from patients might warrant use as a potential biomarker predicting response to therapy with Asunercept. We are currently developing a specific and sensitive assay to quantify CpG2 methylation considered as a companion diagnostic for further clinical studies.